(untitled) (Journal of Engineering, 2023)
The process of risk assessment in the build-operate transfer (BOT) project is very important to identify and analyze the risks in order to make the appropriate decision to respond to them. In this paper, AHP Technique was used to make the appropriate decision regarding response to the most prominent risks that were generated in BOT projects, which includes a comparison between the criteria for each risk as well as the available alternatives and by mathematical methods using matrices to reach an appropriate decision to respond to each risk.Ten common risks in BOT contracts are adopted for analysis in this paper, which is grouped into six main risk headings.The procedures followed in this paper are the questionnaire method to assign the weights of each criterion and each alternative based on the evaluations of 10 experts in BOT contracts after building the questionnaire model.The appropriate decision was reached to respond to each risk, and then the best measures taken were made based on literature reviews of previous research regarding the procedures for risk response plans.